2002
DOI: 10.1006/dbio.2002.0621
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor AP-2 Is an Essential and Direct Regulator of Epidermal Development in Xenopus

Abstract: Expression of the Xenopus homolog of the mammalian transcription factor AP-2alpha (XAP-2) is activated throughout the animal hemisphere shortly after the midblastula transition, and becomes restricted to prospective epidermis by the end of gastrulation, under the control of BMP signal modulation. Elevated expression in the future neural crest region begins at this time. Ectopic expression of XAP-2 can restore transcription of epidermal genes in neuralized ectoderm, both in ectodermal explants and in the intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 46 publications
4
119
0
Order By: Relevance
“…We show that cKer14 expression generally overlapped with cAP2γ ( Figure 4) and that AP2γ was sufficient and necessary for the expression of epidermal markers in the future epidermis (Figures 2 and 5). cKer14 may be one of the earliest markers for primarily committed epidermal progenitors in chick ectodermal patterning and AP2γ might act upstream of cKer14 to initiate epidermal differentiation in face ectoderm [34,52,69]). …”
Section: Discussionmentioning
confidence: 99%
“…We show that cKer14 expression generally overlapped with cAP2γ ( Figure 4) and that AP2γ was sufficient and necessary for the expression of epidermal markers in the future epidermis (Figures 2 and 5). cKer14 may be one of the earliest markers for primarily committed epidermal progenitors in chick ectodermal patterning and AP2γ might act upstream of cKer14 to initiate epidermal differentiation in face ectoderm [34,52,69]). …”
Section: Discussionmentioning
confidence: 99%
“…The promoter regions of keratin 14 were targets of AP2 (Leask et al, 1991;Sinha et al, 2000), AP-1, Ets (Sinha et al, 2000), CACCC-Box binding protein, SP1 (Sinha and Fuchs, 2001), and Skn-1a (Sugihara et al, 2001). AP-1 and AP2 were also involved as the transcription factors in the early epidermal development of Xenopus (Luo et al, 2002;Peng et al, 2002). There have been studies on the relationship of the expression of 63-kDa keratin gene with that of AP2 and Sp1 during metamorphosis (French et al, 1994;Miller, 1995, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…30 In blastula and early gastrula stage Xenopus embryos, tfap2a is expressed in the entire non-neural ectoderm and the prospective NPB territory and a recent study showed that this expression depends on BMP activity. 31,32 The source of BMP ligands is likely the non-neural ectoderm or the prospective NPB ectoderm itself, which expresses BMP ligands in zebrafish, frog, chick and mouse embryos. 28,[33][34][35] Consistently, the potential of epidermis to induce NPB or NC is supposedly attributable to the expression of BMP ligands.…”
Section: Bmp Signalingmentioning
confidence: 99%